An Improved numerical manifold method model for groundwater flow problems. (1st April 2021) - Wang, Yuan; Zhou, Lingfeng; Feng, Di
Abstract: This paper presents an improved numerical manifold method (NMM) model for groundwater flow problems. Hermite interpolation is adopted to construct NMM approximation in order to enhance the accuracy and convergence. Therefore, the new model can achieve accurate solution with C 1 continuity in coarse mesh. Compared with conventional high-order NMM, the proposed method is free from linear dependance problem with even better accuracy and convergence. In addition, a local-refined mesh is used to interpolate detail information of the solution without significantly increasing computation time. The accuracy and convergence of the improved NMM model for groundwater flow problems are demonstrated by several examples.